2011
DOI: 10.1002/erv.1098
|View full text |Cite
|
Sign up to set email alerts
|

Decision‐making Impairments in Women with Binge Eating Disorder in Comparison with Obese and Normal Weight Women

Abstract: This study demonstrates that patients with BED display decision-making deficits on the IGT comparable with other forms of disordered eating. Future research should focus on unravelling the processes underlying the deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
1
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 44 publications
8
83
1
4
Order By: Relevance
“…These results are consistent with several behavioral studies showing that poor decision-making scores measured by the IGT are found in obese, patients with binge eating disorders, and overweight adolescents (Pignatti et al, 2006; Brogan et al, 2010; Verdejo-Garcia et al, 2010; Danner et al, 2012; Fagundo et al, 2012). They are also consistent with previous reports that performance on the IGT was related to the magnitude of weight loss in a diet-induced weight loss intervention in overweight women (Witbracht et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are consistent with several behavioral studies showing that poor decision-making scores measured by the IGT are found in obese, patients with binge eating disorders, and overweight adolescents (Pignatti et al, 2006; Brogan et al, 2010; Verdejo-Garcia et al, 2010; Danner et al, 2012; Fagundo et al, 2012). They are also consistent with previous reports that performance on the IGT was related to the magnitude of weight loss in a diet-induced weight loss intervention in overweight women (Witbracht et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…The question is: why do some individuals become insensitive to the future consequences of their unhealthy eating habits and have difficulty making better healthful choices? While some research has found that poorer decision-making capacity may be associated with abnormal eating behaviors, most of these studies have focused on patients with differing forms of eating pathology (Pignatti et al, 2006; Brogan et al, 2010; Danner et al, 2012; Fagundo et al, 2012). In the current study, we evaluate normal individuals who are not medically diagnosed with an eating disorder.…”
Section: Introductionmentioning
confidence: 99%
“…To put it differently, patients suffering from BED make disadvantageous decisions and fail to adapt their behavior in the face of negative consequences. The first few behavioral studies are in accordance with the idea of decision-making impairments in BED (Danner et al, 2012;Davis et al, 2010;Svaldi et al, 2010;Voon et al, 2015).…”
Section: Introductionsupporting
confidence: 64%
“…People with substance abuse disorders exhibited impaired IGT performance in the absence of impaired delaydependent memory or executive functioning (Gonzalez et al, 2007;Quednow et al, 2007). Impaired decision-making on the IGT has also been observed in people with binge eating disorder and sufferers of alcoholism (Danner et al, 2012;Le Berre et al, 2014). Similarly, patients with schizophrenia also exhibit deficient IGT performance (Kim et al, 2009;Wasserman et al, 2012;Brambilla et al, 2013;Fond et al, 2013), although this finding has not been consistently observed (Turnbull et al, 2006).…”
Section: Impaired Decision-making Across Neuropsychiatric Populationsmentioning
confidence: 91%